Clear sky global solar irradiance on tilt angles of photovoltaic module in Perlis, Northern Malaysia - Ismail, Daut, Prof. Dr.; Muhammad Irwanto; Mohd Irwan, Yusoff; Gomesh Nair, Shasidharan; Noor Syafawati, Ahmad (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/